Labour demand and the distribution of wages in South African manufacturing exporters - Marianne Matthee; Neil Rankin; Carli Bezuidenhout (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper contributes to the understanding of the linkages between exporting, labour demand, and wages in South Africa. We disentangle labour market differences between exporters and non-exporters and find that exporters employ more people and pay higher wages. Given these higher wages we investigate how this wage premium is distributed within the exporting firm. There appears to be a wide dispersion of wages within exporters (particularly international/non-African exporters). However, almost all of that dispersion (particularly amongst continuing exporters) is explained by the labour productivity and size of these firms. This suggests that there is thus a large degree of dispersion for these variables for these firm groups (relative to non-exporters). Wage inequality within exporters is not driven by exporting but rather by characteristics associated with the types of firms which participate in the export market.
Keywords: F10; F14; 330; exporters; firm-level data; labour demand; wages; inequality; South Africa